The Impact of Investing in Renewable Energy Projects on the Financial Performance of Jordanian Eelectricity Companies since 2017 - Alyasein, Bayan Ahmad (Journal of Economic, Administrative and Legal Sciences, 2023)
This study aimed to know the impact of investment in Renewable energy projects on the financial performance represented in (profitability, degree of liquidity, solvency) for electricity companies and the study population consisted of employees working in the Department of Finance of the main administration of electricity companies represented in (National Electricity Company for Public Shareholding, Jordan Electricity Company for Public Shareholding Limited, Electricity Distribution Company for Public Shareholding Limited, Irbid Governorate Electricity Company for Public Shareholding Limited), and The study sample consisted of (120) financial employees working in the main administration of electricity companies. And the researcher used the statistical program (SPSS) to analyze the study tool, and the results of the study showed that there is a statistically significant effect at the significance level (α≤0.05) for investing in Renewable energy projects on the financial performance represented in (profitability, degree of liquidity, solvency). For electricity companies, the study recommended the necessity of having legislation obligating the Ministry of Energy to cooperate with researchers by giving them information on costs to know the true value of the costs of Renewable energy projects, so as to provide information for use in future research.